2003
DOI: 10.1007/s00776-003-0705-z
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional gait analysis of adults with hip dysplasia after rotational acetabular osteotomy

Abstract: Dysplasia of the hip, the most common cause of secondary coxarthrosis, has a relatively high prevalence in Japan. Rotational acetabular osteotomy (RAO) is an interventional strategy that seeks to reduce the abnormal amount of high stress concentration in the acetabulum and thereby to prevent the development of coxarthrosis. Long-term clinical results have been reported, but functional evaluations of the gait before and after RAO are underreported. The aim of our recently initiated long-term prospective study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Previous reports have noted patients with hip dysplasia have increased flexion and reduced hip flexor moment [10,19,28,30]. Pedersen et al [27] initially reported this finding in a group of adult women with hip dysplasia after treatment with a PAO.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous reports have noted patients with hip dysplasia have increased flexion and reduced hip flexor moment [10,19,28,30]. Pedersen et al [27] initially reported this finding in a group of adult women with hip dysplasia after treatment with a PAO.…”
Section: Discussionmentioning
confidence: 89%
“…Gait analysis in adult patients with dysplasia has shown the decreased acetabular weightbearing zone and the lateralized joint center affect the joint contact pressures [1,10,24,27,28,30]. There are no studies, however, that have specifically assessed the kinematics and kinetics of the hip in adolescent and young adult patients undergoing a PAO who have been treated with a previous pelvic osteotomy.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo and in vitro studies have shown hip joint forces during gait are directed superoposterior at heel strike (Bergmann et al, 2001;Endo et al, 2003; (Maeyama et al, 2008). However, these investigators did not specify the gait cycle phase in which the accelerations were observed.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The major factors are mechanical stress and dynamic instability, and if these are not improved after surgery the outcome will not be good. Although many reports have shown that periacetabular osteotomy can reduce contact stress in the hip joint, 17,18,20,21 no studies have clarified whether it can also reduce instability of the hip joint during routine walking. Our results indicate that the femoral head moves in the superior, posterior and lateral directions while walking under conditions encountered in routine daily life, and that mechanical stress to the acetabulum can be expected in the posterosuperior direction in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…5 Various types of periacetabular osteotomy are used in patients who are too young for total hip replacement. [13][14][15][16][17][18][19] We perform a curved periacetabular osteotomy, 16 which is a modification of the Bernese periacetabular osteotomy developed by Ganz et al 13 Although many reports have shown that periacetabular osteotomy can reduce contact stress in the hip joint, [20][21][22][23][24] none have clarified whether it can also reduce instability during walking in daily life. After our previous study 7 we hypothesised that dynamic instability of the hip joint would be reduced if the cover of the femoral head was improved by periacetabular osteotomy.…”
mentioning
confidence: 99%